How do I Imagine Orthodontic World in 2035 - Acharya, Swati Saraswata; Mohanty, Pritam; Rao, Pavithra (Orthodontic Journal of Nepal, 2017)
The future orthodontic world is so bright that we definitely ‘need to wear shades’. We are infiltrating a new era of orthodontics accoutered with modern technologies. However, ever growing operating costs, greater patient expectations and indictments against orthodontists are few concerns which need to be addressed. Increased information technology skills, three-dimensional image superimposition methods, custom designed treatments, tooth movement control systems, digital models and evidencebased orthodontics will be the new outlook in the next twenty years. Orthodontic research is entering an epoch of exhilaration. Trends, issues and new evolutions can come together in startling ways. Scenarios are the recitals about the future that combine these forces of change in various ways. Genome wide coalition studies are vital to further the evidence base to practice orthodontics in the coming years.